Microwave Hyperthermia Technology Based on Near‐Field Focused Metasurfaces: Design and Implementation - Xiong, Han; Xie, Jin‐Yun; Liu, Yu‐Jie; Wang, Ben‐Xin; Xiao, Dong‐Ping; Zhang, Huai‐Qing (Advanced functional materials, 2025)
This paper presents a near‐field focused metasurface design method for microwave hyperthermia. Utilizing full‐wave electromagnetic simulation, a novel dual‐layer metasurface unit with the following characteristics is developed: transmission efficiency higher than −1 dB, adjustable transmission phase from 0° to 360°, and insensitivity to the polarization and incident angle of the incoming wave. Leveraging phase compensation theory, the units at different positions in the array to achieve near‐field focusing functionality is meticulously designed. To further optimize transmission efficiency, the transmission phase of the central unit of the metasurface to 76° is tuned. When applying this near‐field focused metasurface to microwave hyperthermia, the electromagnetic and thermal effects in biological tissues is conducted simulations and experiments to analyzed. The results demonstrate that the proposed metasurface can effectively focus microwave energy, achieving efficient microwave transmission in pork tissue and generating localized high temperatures in the target area. This research introduces new design concepts and implementation strategies for the development of microwave hyperthermia technology. A novel metasurface‐enhanced microwave hyperthermia system designed for precise tissue heating. A double‐ridged horn antenna emits microwave radiation, which is then focused by a metasurface onto the targeted tissue area. The metasurface is engineered to achieve high transmission efficiency and effective near‐field focusing, ensuring precise thermal treatment of superficial tumors while minimizing exposure to surrounding healthy tissue.